THE INFLUENCE OF IMPORT CONTAINER FLOW AND BOX/CRANE/HOUR ON IMPORT CONTAINER DWELLING TIME AT SEMARANG CONTAINER TERMINAL - Prima Mareta Valentonia; Karnowahadi - Karnowahadi; Paniya - Paniya (Admisi dan Bisnis, 2018)
The study has purposes to analyze the influence of import container flow (AIC) and box/crane/hour (BCH) on the import container dwelling time (ICDT) at Semarang Container Terminal (TPKS). The analysis tool uses Multiple Regression conducted Classical Analysis Test. The study use secondary data that obtained from TPKS such as monthly report of import container flow, monthly report of box/crane/hour and monthly report of import container dwelling time.The study has significant levelα = 0,05for simultaneously and partially on the import container dwelling time atTPKS. The result of F-test shows that F sig. value (0.000) less than significance level α (0,05), that means import container throughput and box/crane/hour have significant influence on the import container dwelling time at TPKS. While the result of Multiple Regression Analysis was ICDT = 37,148 – 2,352 LnAIC– 0,331 BCH. The result of Multiple Regression Analysis shows that regression coefficients of import container flow and box/crane/hour have negatively influenceon import container dwelling time. Coefficient regression of import container flow= -2,352, that explains if import container flowincreases by 1%, the number of import container dwelling time would decrease by 2,352 days. Then coefficient regression of box/crane/hour= 0,331, that means if there is an increase of box/crane/hour by 1 box/hour, the import container dwelling time will decreases by 0,331 day. While the result of Coefficient of Determination (R2) = 0,323 or 32,3%, it means that dwelling time factor  at TPKS is 32,3% explain by import container flows and box/crane/hour